Effects of High Intensity Resistance Training Versus Whole-Body Electromyostimulation on Cardio-Metabolic Risk Factors in Untrained Middle Aged Males. A Randomized Controlled Trial - Kemmler, Wolfgang; Kohl, Matthias; Stengel, Simon Von (Journal of Sports Research, 2016)
Background: Time-efficient exercise protocols may encourage subjects to exercise more frequently and could thus be excellent tools for health promotion. The aim of this study was to compare the effectiveness of the time-efficient methods HIT and/versus WB-EMS on cardio-metabolic risk factors in untrained middle-aged males. Methods: Untrained, healthy males (30-50 years) were randomly allocated either to 16-weeks of WB-EMS with 3 applications of 20 min/2 weeks, or 16 weeks of high intensity (resistance) training (HIT) performing 2 sessions/week. Both methods addressed all the main muscle groups. Metabolic-Syndrome Z-Score (MetS-Z-Score), abdominal body fat and total cholesterol/HDL-cholesterol (TC/HDL-C) were defined as the study endpoints. Results: HIT and WB-EMS were similar (p≤.096) effective to improve the MetS-Z-Score (HIT: p=.031 vs. WB-EMS: p=.001) and abdominal body fat (HIT: -4.5±8.1%, p=.014 vs. WB-EMS -4.0±5.2%, p=.002) in this cohort. No significant changes (HIT: -2.7±7.4, p=. 216 vs. WB-EMS: -2.2±10.2 p=.441) or group-differences (p=.931) within and between the groups were determined for TC/HDL-C. Conclusion: WB-EMS and HIT-RT is equally effective, attractive, feasible and time-efficient methods for combatting cardio-metabolic risk factors in untrained middle-aged males. WB-EMS can be considered as an effective option, particularly for subjects with low time resources unwilling or unable to conduct exhausting HIT protocols.